2003
DOI: 10.1128/jcm.41.5.2249-2254.2003
|View full text |Cite
|
Sign up to set email alerts
|

Babesia bicornis sp. nov. and Theileria bicornis sp. nov.: Tick-Borne Parasites Associated with Mortality in the Black Rhinoceros ( Diceros bicornis )

Abstract: A novel Babesia species, designated Babesia bicornis sp. nov., was identified in three black rhinoceroses (Diceros bicornis) that died in wildlife areas in Tanzania and South Africa. Screening of black rhinoceroses in South Africa revealed, in addition to B. bicornis, a second parasite, designated Theileria bicornis sp. nov. CASE REPORT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(185 citation statements)
references
References 7 publications
8
176
0
1
Order By: Relevance
“…Theileria bicornis, carried by 52.6% nyalas in this survey, was originally described from healthy black rhinoceroses in South Africa and is not known to be pathogenic (Nijhof et al 2003). Theileria bicornis was also described in 36.4% of white rhinoceroses (Ceratotherium simum) from the Kruger National Park and in 3.8% of cattle tested in Uganda (Govender 2009, Muhanguzi et al 2010.…”
Section: Theileria Bicornismentioning
confidence: 99%
See 2 more Smart Citations
“…Theileria bicornis, carried by 52.6% nyalas in this survey, was originally described from healthy black rhinoceroses in South Africa and is not known to be pathogenic (Nijhof et al 2003). Theileria bicornis was also described in 36.4% of white rhinoceroses (Ceratotherium simum) from the Kruger National Park and in 3.8% of cattle tested in Uganda (Govender 2009, Muhanguzi et al 2010.…”
Section: Theileria Bicornismentioning
confidence: 99%
“…High seroprevalence of Anaplasma species, ranging from 75 to 100%, was found in wildlife at the livestock-wildlife interface in Kenya (Ngeranwa et al 2008). Species examined were eland, blue wildebeest, kongoni (Damaliscus (Nijhof et al 2003;Nijhof et al 2005;Oosthuizen et al 2008;Oosthuizen et al 2009). …”
Section: Anaplasma Marginalementioning
confidence: 99%
See 1 more Smart Citation
“…The reverse line blot (RLB) method (Gubbels et al 1999), based on simultaneous detection of the 18S rRNA gene for various Babesia and Theileria species, has been extensively used for surveillance purposes (Georges et al 2001; AlmerƬa et al 2002;Oura et al 2004;Nijhof et al 2003Nijhof et al , 2005Altay et al 2007;M'ghirbi et al 2008;Altay et al 2008;Matjila et al 2008;Oosthuizen et al 2008; AlmerƬa et al 2009;Salih et al 2010;Yusufmia et al 2010; Tomassone et al 2012;Ceci et al 2014;Githaka et al 2014;Eygelaar et al 2015;Njiiri et al 2015). The method relies on the amplification of the V4 hypervariable region of the 18S rRNA gene, followed by hybridization to probes for various The current study aimed to assess whether other genotypes may be amplified by the primers used in these assays, since it was shown that multiple templates may affect sensitivity of the diagnostic assays (Pienaar et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Theileria taurotragi infection has been reported to be fatal in eland (Taurotragus oryx), although infections in cattle are usually subclinical and not readily detected (Grootenhuis et al, 1979 andGrootenhuis et al, 1980). Babesia bicornis was identified in four fatal cases of babesiosis in black rhinoceros (Diceros bicornis) in South Africa and Tanzania (Nijhof et al, 2003). Three of the four rhinoceros died soon after capture, during periods of nutritional or pregnancy-related stress, or during extreme climatic conditions.…”
Section: Introductionmentioning
confidence: 99%